Prediction of fibrosis progression in chronic viral hepatitis - Wong, Grace Lai-Hung (Clinical and molecular hepatology, 2014)
Prediction of liver fibrosis progression has a key role in the management of chronic viral hepatitis, as it will be translated into the future risk of cirrhosis and its various complications including hepatocellular carcinoma. Both hepatitis B and C viruses mainly lead to fibrogenesis induced by chronic inflammation and a continuous wound healing response. At the same time direct and indirect profibrogenic responses are also elicited by the viral infection. There are a handful of well-established risk factors for fibrosis progression including older age, male gender, alcohol use, high viral load and co-infection with other viruses. Metabolic syndrome is an evolving risk factor of fibrosis progression. The new notion of regression of advanced fibrosis or even cirrhosis is now strongly supported various clinical studies. Even liver biopsy retains its important role in the assessment of fibrosis progression, various non-invasive assessments have been adopted widely because of their non-invasiveness, which facilitates serial applications in large cohorts of subjects. Transient elastography is one of the most validated tools which has both diagnostic and prognostic role. As there is no single perfect test for liver fibrosis assessment, algorithms combining the most validated noninvasive methods should be considered as initial screening tools.